도로와의 이격거리를 고려한 철도사업의 환경생태적 영향 최소화 방안에 대한 연구 - 김민경(Min Kyeong Kim); 김동엽(Dong Yeob Kim) (Ecology and Resilient Infrastructure, 2020)
Railroads and roads are typical linear projects, and their networks are expanding nationwide. To minimize the impact of their development on the environment, ecological disconnection due to the parallel lines of railroads and roads is to be avoided as much as possible. In this study, to examine the environmental impact of railroad and road development, the characteristics of railroads and roads and the differences between them were examined through a comparative analysis of key evaluation items. Based on the result, the road development, unlike the railroad project, suggests items for establishing an efficient land use plan and soil protection as the key evaluation items. There are no specific evaluation items and criteria that can be used to examine the environmental impact of railroad lines located adjacent to roads. In this study, eight evaluation items were suggested by reviewing the relevant literature. In particular, in the strategic environmental impact assessment stage, which examines the adequacy and location feasibility of the plan, the minimum separation distance criteria were proposed to examine in advance the environmental impact of railroads located adjacent to the existing roads. The distances were examined for the previously operated routes, and a distance of less than 200 m was suggested to minimize the environmental impact. The results were compared with those in other studies and analyzed. The results of this study can be used as a basis for examining alternative routes that can minimize the environmental impact of adjacent railroads and roads. 철도와 도로는 대표적인 선형사업으로, 전국적으로 철도망과 도로망이 확대되고 있는 추세이며, 환경에 미치는 영향을 최소화하기 위해 철도와 도로의 평행노선에 따른 생태계 단절을 최대한 지양하고 있다. 본 연구에서는 우선적으로 철도와 도로개발 시, 환경에 미치는 영향을 살펴보기 위한 각 사업의 중점평가항목에 대한 비교·분석을 통해 차이점과 특징을 고찰하였다. 그 결과, 도로 개발은 철도사업과는 달리 효율적인 토지이용계획 수립에 대한 사항과 토양 보호를 중점평가항목으로 제시하고 있다. 본 연구에서는 철도 노선이 도로와 인접하게 될 때의 환경적 영향을 살펴보기 위한 구체적인 평가 항목과 기준이 제시되어 있지 않음에 따라, 관련 문헌을 검토하여 총 8개 평가 항목을 제시하였다. 특히, 계획의 적정성과 입지타당성을 살펴보기 위한 전략환경영향평가 단계에서 기존의 도로에 철도가 인접하게 될 때 미치는 환경적 영향을 사전에 검토할 수 있는 이격거리 기준을 제안하고자, 기 운영 중인 철도 노선을 대상으로 도로와의 이격거리를 살펴보았으며, 환경생태적 영향을 최소화하기 위해 검토해야 할 이격거리로 200 m 이내일 것을 제시하였다. 본 연구 결과는 철도와 도로가 인접할 때 환경생태적 영향을 최소화할 수 있는 대안노선을 검토하는 사업계획 단계에서 근거 자료로 활용될 수 있을 것이다.